MOMENT registry: Patients with advanced non-small-cell lung cancer harboring MET exon 14 skipping treated with systemic therapy - Thomas, Michael; Christopoulos, Petros; Iams, Wade T.; Mazières, Julien; Cortot, Alexis B.; Peled, Nir; Minuti, Gabriele; Smit, Egbert F.; Audhuy, Francois; Berghoff, Karin; Eggleton, S. Peter; Fries, Frank; et al. (Journal of Comparative Effectiveness Research, 2025)
Aim: MET exon 14 (METex14) skipping occurs in 3–4% of non-small-cell lung cancer (NSCLC) cases. Low frequency of this alteration necessitated open-label, single-arm trials to investigate MET inhibitors. Since broad MET biomarker testing was only recently introduced in many countries, there is a lack of historical real-world data from patients with METex14 skipping NSCLC receiving conventional therapies. Given the rarity of this population and limitations of existing real-world data sources, the MOMENT registry aims to prospectively collect uniform, comprehensive, high-quality data from patients with METex14 skipping advanced NSCLC treated in routine clinical practice, which can support clinical and regulatory decision making. Patients & methods: MOMENT is a multinational, non-interventional disease registry collecting data on patients with METex14 skipping advanced NSCLC receiving any systemic anticancer therapy. Newly diagnosed patients and those already receiving treatment are eligible. Patients with previous participation in a clinical trial can be included if they receive at least one subsequent therapy line in a routine clinical setting. Eligible systemic treatment includes all available anticancer therapies (approved, conditionally approved or provided through Early Access). Data collection includes biomarker testing results, demographics, baseline clinical characteristics, treatment details and effectiveness, safety information and imaging. Registry site inclusion is dependent on confirmation that local METex14 skipping detection methods are sufficient to confirm METex14 skipping status. MOMENT is currently active at more than 60 sites across Europe and North America and approximately 700 patients are expected to be enrolled within the next 4 years. The first patient was enrolled on 4 October 2022. After completion of data collection, MOMENT data can be shared with external parties to conduct non-interventional studies. Discussion/conclusion: The MOMENT registry collects comprehensive, high-quality real-world data from patients with METex14 skipping advanced NSCLC receiving systemic anticancer treatment in a routine clinical setting, to enable future studies informing regulatory decisions and optimal care for this rare population